Gallensteine – interdisziplinäre Behandlung - Scherber, Philipp Robert; Zúniga, Silvia Eugenia; Glanemann, Matthias; Lammert, Frank (DMW - Deutsche Medizinische Wochenschrift, 2020)
Gallstones develop in the gallbladder or the bile ducts. According to their chemical composition, gallstones can be divided into cholesterol stones, which are common, and the rare bile pigment stones. Altogether, up to 20 % of all adults develop gallstones and more than 20 % of them symptoms or complications. Female sex, age, pregnancy, physical inactivity, obesity, overnutrition and genetic factors such as ABCB4 deficiency of the hepatic lecithin transporter are kown risk factors for gallstone formation. In about one half of all patients biliary symptoms precede the three common and potentially life-threatening complications (acute cholecystitis, acute cholangitis and biliary pancreatitis). Although our knowledge about the genetics and pathophysiology of gallstones has improved, current treatment algorithms are predominantly invasive (ERC and surgery). Thus, better strategies are needed to prevent the formation of gallstones in general.
Keywords: Gallensteinleiden; akute Cholezystitis; Cholezystolithiasis; biliäre Pankreatitis; Cholezystektomie